Faith, hope, and Ivy June [compact disc, unabridged] - Naylor, Phyllis Reynolds (Random House, 2009)
During a student exchange program, seventh-graders Ivy June and Catherine share their lives, homes, and communities, and find that although their lifestyles are total opposites they have a lot in common.